Strategi Guru Sejarah terhadap Pelaksanaan Kurikulum Merdeka dalam Pembelajaran Sejarah di SMAN 12 Semarang - Utami, Indarti Tri; Amin, Syaiful (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to explain the strategies that can be applied by history teachers in implementing the Merdeka Curriculum in history education at SMA Negeri 12 Semarang. By understanding the school context, which includes its founding history, vision, and educational programs, this study identifies relevant strategies to enhance the effectiveness of history education. Data were collected through document analysis and interviews with experienced history teachers at SMA Negeri 12 Semarang. The results indicate that a deep understanding of the Merdeka Curriculum, development of contextual teaching materials, interactive teaching approaches, technology integration, competency-based evaluation, collaboration with other teachers and communities, and continuous professional development are key to the successful implementation of the Merdeka Curriculum in history education at SMA Negeri 12 Semarang.